Ramie (Boehmeria Nivea) as Phytoremediation Crop for Heavy Metal-contaminated Paddy Soil in Southern China: Variety Comparison, Cd Accumulation, and Assessment of Fiber Recycling. Issue 15 (23rd November 2022) - Wu, Zhimin; Tang, Qingming; Wang, Yufu; Qiu, Caisheng; Long, Songhua; Zhao, Xinlin; Hu, Zhixin; Guo, Yuan
ABSTRACT: Ramie ( Boehmeria nivea ) is an economic fiber crop that is specifically produced in southern China and faces heavy metal pollution of arable soil. This study investigated the phytoextraction of cadmium (Cd) in seven ramie cultivars, including uptake, translocation, and accumulation differences in organs among cultivars, and assessed the safety of fiber for human health. The obtained results demonstrated that: (1) Zhongzhu No. 3 exhibited the best yield performance, with a fresh bast weight of approximately 343 g in a medium Cd-contaminated paddy field. Leaves accounted for the largest biomass among the parts investigated. (2) Phloem exhibited the highest Cd concentration. Low accumulation and reasonable allocation of Cd enhanced the resistance of ramie to Cd. (3) All varieties exhibited more than 90% Cd removal percentage during the stripping process of fibers. The Cd concentration of the fiber was significantly lower than that of the standard for the fiber industry. Our study provides a new direction for variety breeding in Cd-resistant plants.